Global analysis of the sugarcane microtranscriptome reveals a unique composition of small RNAs associated with axillary bud outgrowth - Ortiz-Morea, Fausto A. [UNESP]; Vicentini, Renato; Silva, Geraldo F.F. [UNESP]; Silva, Eder M. [UNESP]; Carrer, Helaine; Rodrigues, Ana P. [UNESP]; Nogueira, Fabio T.S. [UNESP] (Oxford University Press (OUP), 2013)
Axillary bud outgrowth determines shoot architecture and is under the control of endogenous hormones and a fine-tuned gene-expression network, which probably includes small RNAs (sRNAs). Although it is well known that sRNAs act broadly in plant development, our understanding about their roles in vegetative bud outgrowth remains limited. Moreover, the expression profiles of microRNAs (miRNAs) and their targets within axillary buds are largely unknown. Here, we employed sRNA next-generation sequencing as well as computational and gene-expression analysis to identify and quantify sRNAs and their targets in vegetative axillary buds of the biofuel crop sugarcane (Saccharum spp.). Computational analysis allowed the identification of 26 conserved miRNA families and two putative novel miRNAs, as well as a number of trans-acting small interfering RNAs. sRNAs associated with transposable elements and protein-encoding genes were similarly represented in both inactive and developing bud libraries. Conversely, sequencing and quantitative reverse transcription-PCR results revealed that specific miRNAs were differentially expressed in developing buds, and some correlated negatively with the expression of their targets at specific stages of axillary bud development. For instance, the expression patterns of miR159 and its target GAMYB suggested that they may play roles in regulating abscisic acid-signalling pathways during sugarcane bud outgrowth. Our work reveals, for the first time, differences in the composition and expression profiles of diverse sRNAs and targets between inactive and developing vegetative buds that, together with the endogenous balance of specific hormones, may be important in regulating axillary bud outgrowth. © 2013 © The Author(2) [2013].
Keywords: microRNAs; phytormones; small RNAs; sugarcane; vegetative axillary buds